Simulation And Performance Studies Of Thermally Efficient Light Emitting Diodes Drivers - Mohd Supian, Norazlina (2018)
The thermal behaviour of an electronic package is often characterized by evaluating the junction temperature and thermal resistance at the junction of a single or multiple heat source to ambient. In the case of IC LED drivers, the heat source within the device is either single or multiple due to presence of many integrated component such as transistor, internal resistor, etc on a single die. Hence the evaluation of IC drivers with single or multiple heat sources is absolutely necessary for imparting suitable thermal management within the device. In this study, thermal transient measurement method and computational fluid dynamics (CFD) simulations have been used to measure thermal resistance and junction temperature.